(untitled) (Journal of the College of Education for Women, 2022)
The research aims to study some of the human characteristics of the state of Singapore to know the impact of these characteristics on the strength of the state, its development and. The research included two aspects, theoretical and analytical, using the descriptive analytical method, force analysis method, as well as the historical method. The data was analyzed according to mathematical equations, including the size of the country’s population, the extraction of the population growth rate and the concept of age structure, where some indicators related to this concept have been explained. The researcher reached a set of results, the most important of which were: that the population size of the state of Singapore in the period between (1970 - 2020) has been on a continuous increase since its independence. However, it has adopted a population policy that suits the area of ​​the state for the period (2010-2020). The increase continued to rise to reach (665,609, 7,570,240, and 861,7474 people) for the years (2030, 2040 and 2050), respectively. This is an indication of a real transformation of the demographic contribution, which constitutes a powerful factor that gives the state an influential position in international regional relations and a support for the demographic revolution despite the small area of ​​the Republic of Singapore. The results of the research also showed instability in population growth rates during the past fifty years, ranging between the lowest growth rate of 1.3% and the highest growth rate of 2.9% for the period between (1970 - 2020). Accordingly, the population increase in Singapore is not only related to natural increase, but is greatly affected by the factor of external migration, whose effects became clear during the last period of (2010-2020).